2005
DOI: 10.1210/jc.2005-0151
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Endothelial Dysfunction in Young Women with Polycystic Ovary Syndrome

Abstract: Women with PCOS have significant endothelial dysfunction at an early age (i.e. early 20s), and largely independent of obesity. This suggests that women with PCOS are at increased risk for early onset cardiovascular disease and may gain particular benefit from measures to improve endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
81
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 42 publications
11
81
5
Order By: Relevance
“…It is a cheap, repeatable, and non-invasive measure of endothelial function and provides a unique opportunity for early assessment of possible treatment benefit, complementing endpoints of structural arterial disease and cardiovascular outcomes that take much longer and are more expensive to study (23). We found endothelial dysfunction in young nonobese PCOS patients, which is in concordance with previously published data (12). This suggests that even non-obese PCOS patients have an increased risk for CVD and may gain particular benefit from treatment that improves endothelial function.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is a cheap, repeatable, and non-invasive measure of endothelial function and provides a unique opportunity for early assessment of possible treatment benefit, complementing endpoints of structural arterial disease and cardiovascular outcomes that take much longer and are more expensive to study (23). We found endothelial dysfunction in young nonobese PCOS patients, which is in concordance with previously published data (12). This suggests that even non-obese PCOS patients have an increased risk for CVD and may gain particular benefit from treatment that improves endothelial function.…”
Section: Discussionsupporting
confidence: 91%
“…Nitrate-mediated vasodilatation was also impaired in PCOS patients compared with control women, in agreement with previous studies (12). The vasodilatory response to GTN is considered to be a function of both vascular smooth muscle relaxation (direct action of GTN on the vascular smooth muscle) and the endothelial response to hyperemia caused by GTNinduced dilatation of the resistance vessels.…”
Section: Parametersupporting
confidence: 91%
See 1 more Smart Citation
“…In 2 studies, there was no association, 151,188 whereas other studies reported significant associations of testosterone with endothelial dysfunction. 153,154,189 In contrast, an inverse association of the adrenal androgen dehydroepiandrosterone sulfate has been seen with carotid intimamedia thickness in PCOS. 145,152 Multiple intervention studies have shown that therapy that increases insulin sensitivity can improve endothelial function 190,191 more than oral contraceptives 192 and in combination with oral contraceptives.…”
Section: The Influence Of Sex Hormones On Cardiovascular Risk In Pcosmentioning
confidence: 95%
“…Endothelial dysfunction was shown to be associated with higher levels of androgens and with insulin resistance (202). This was observed even at very early ages, and with a trend of deterioration of endothelial function from lean to overweight and obese PCOS women (203). A recent systematic review of the studies has confirmed that C-IMT was thicker in women with PCOS in comparison with controls (204).…”
Section: Subclinical CV Disease In Pcosmentioning
confidence: 99%